2022
DOI: 10.1021/acs.chemmater.2c02807
|View full text |Cite
|
Sign up to set email alerts
|

Mixology of MA1–xEAxPbI3 Hybrid Perovskites: Phase Transitions, Cation Dynamics, and Photoluminescence

Abstract: Mixing molecular cations in hybrid lead halide perovskites is a highly effective approach to enhance the stability and performance of optoelectronic devices based on these compounds. In this work, we prepare and study novel mixed 3D methylammonium (MA)−ethylammonium (EA) MA 1−x EA x PbI 3 (x < 0.4) hybrid perovskites. We use a suite of different techniques to determine the structural phase diagram, cation dynamics, and photoluminescence properties of these compounds. Upon introduction of EA, we observe a gradu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
42
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(50 citation statements)
references
References 75 publications
7
42
1
Order By: Relevance
“…This agrees with that observed for the GA x MA 1– x PbI 3 system . It should also be noted that the O → T transition temperature is progressively reduced with increasing x in the EA x MA 1– x PbI 3 system . This shows that different cations can cause contrasting changes in the relative stability of different structures of a perovskite.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…This agrees with that observed for the GA x MA 1– x PbI 3 system . It should also be noted that the O → T transition temperature is progressively reduced with increasing x in the EA x MA 1– x PbI 3 system . This shows that different cations can cause contrasting changes in the relative stability of different structures of a perovskite.…”
Section: Resultssupporting
confidence: 89%
“…Hence, considering Figure a,b and the aforementioned discussion, it can be inferred that the disappearance of the orthorhombic phase is accompanied by a peak in ε″( T ) curve, while the appearance of the tetragonal phase is accompanied by a rapid increase in ε′( T ). It should be noted that this increase in ε′( T ) is much more subtle in FA0.10 than in MAPbI 3 , as evidenced by the peak’s broadening, which might be associated with the change (restriction) in the rotation of the MA + cations when mixing with other cations, as already proposed for the FA x MA 1– x PbI 3 system and others, such as EA x MA 1– x PbI 3 , FA x MA 1– x PbBr 3 and DMA x MA 1– x PbBr 3 . In these systems, it is generally shown that the activation energy for the rotation of MA + cations increases, causing a disorder at low temperatures and consequent transition broadening.…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…Recently, the MA 1− x EA x PbI 3 mixed perovskite system, identified in our previous study 4 as one strong candidate for improved stability and photovoltaic performance, was theoretically and experimentally confirmed. 37…”
Section: Quasi-2d Perovskite Structures: Electronic Structure and Sta...mentioning
confidence: 99%